Pintarolas, a tangible sketch application - Dias, J. M. S.; Dehanov, J.; Cabral, C.; Carola, A. (Interacção 2004 - 1ª Conferência Nacional em Interacção Pessoa-Máquina, 2021)
This paper presents Pintarolas, a simple sketch application that uses tangible interfaces as Human-Computer lnteraction modality. Totally sensor-less and cable-less interfaces (ordinary boardmarkers with fiducial markers attached), provide the means to support basic sketching tasks, such as drawing lines and sketching 2D primitive shapes (circle, triangle and square). The system requires an ordinary video camera linked to a PC and uses AR Toolkit for the handling of the Tangible Interfaces. Open GL is used for the graphical output and the CALI library, normally used for Calligraphic user interfaces development, is adopted in our case for 2D primilive shape recognition. A simple usability test was developed to assess the feasibility of this novel user interface in simple sketching tasks, showing that the users found the concept interesting and the tangible interfaces easy to operate.